2014
DOI: 10.1051/0004-6361/201322099
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity evolution, metallicity gradients, and gas fractions atz~ 3.4

Abstract: We used near-infrared integral field spectroscopic observations from the AMAZE and LSD ESO programs to constrain the metallicity in a sample of 40 star-forming galaxies at 3 < z < 5 (most of which are at z ∼ 3.4). We measured metallicities by exploiting strong emission-line diagnostics. We found that a significant fraction of star-forming galaxies at z ∼ 3.4 deviate from the fundamental metallicity relation (FMR), with a metallicity of up to a factor of ten lower than expected according to the FMR. This deviat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

36
329
3
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(375 citation statements)
references
References 109 publications
(197 reference statements)
36
329
3
7
Order By: Relevance
“…To verify this conclusion with our sample we show in Fig. 9 star-forming galaxies at z > 2 by Cullen et al (2014) (stars), star-forming galaxies at 2.0 < z < 2.6 by Steidel et al (2014) (filled circles), star-forming galaxies at redshifts z ∼ 3.5 by Maiolino et al (2008) (filled squares), star-forming galaxies with z ∼ 2 by Maier et al (2014) (crosses), and star-forming galaxies with z ∼ 3.4 by Troncoso et al (2014) (asterisks). The relation for galaxies with z ∼ 2.3 by Sanders et al (2015) is shown by thick yellow solid line.…”
Section: Stellar Mass -Metallicity Relationsupporting
confidence: 83%
See 3 more Smart Citations
“…To verify this conclusion with our sample we show in Fig. 9 star-forming galaxies at z > 2 by Cullen et al (2014) (stars), star-forming galaxies at 2.0 < z < 2.6 by Steidel et al (2014) (filled circles), star-forming galaxies at redshifts z ∼ 3.5 by Maiolino et al (2008) (filled squares), star-forming galaxies with z ∼ 2 by Maier et al (2014) (crosses), and star-forming galaxies with z ∼ 3.4 by Troncoso et al (2014) (asterisks). The relation for galaxies with z ∼ 2.3 by Sanders et al (2015) is shown by thick yellow solid line.…”
Section: Stellar Mass -Metallicity Relationsupporting
confidence: 83%
“…The location of star-forming galaxies with redshifts 2.0 < z < 2.6 by Steidel et al (2014) and with redshifts z > 2 by Cullen et al (2014) is shown by grey rectangles. Star-forming galaxies with redshifts z ∼ 3.4 by Troncoso et al (2014) are indicated by dark asterisks. (2004) is shown by thin dashed lines and dot-dashed lines are 1σ dispersions.…”
Section: Absolute G-band Magnitude -Metallicity Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameterization of the FMR by Mannucci et al (2010), seems to hold until z < 2, and then it changes substantially at higher redshift (e.g., Mannucci et al 2010;Yabe et al 2012;Ly et al 2014;Troncoso et al 2014;Cullen et al 2014). Variations are expected if the relationship is caused by cosmic gas accretion since accretion rates and IGM metallicities change over time.…”
Section: The Stellar Mass-metallicity-sfr Relationshipmentioning
confidence: 99%